A Systematic Review Exploring the Anticancer Activity and Mechanisms of Glucomannan - Li, Jun-yi; Sun, Fei; Zhou, Hai-feng; Yang, Jia; Huang, Cong; Fan, Heng (Frontiers in Pharmacology, 2019)
Glucomannan, long-recognized as the active ingredient of Traditional Chinese Medicinal Herb Konjac glucomannan, is a naturally-occurring polysaccharide existing in certain plant species and fungi. Due to its special property to also serve as a dietary supplement, glucomannan has been widely applied in clinic to lower body weight, circulation cholesterol level and to treat constipation, diabetes and arterial sclerosis. Besides the regulatory role engaged with gastroenterological and metabolic syndrome, recently, its therapeutic effect and the underlying mechanisms in treating cancerous diseases have been appreciated by mounting researches. The present review aims to emphasize the multifaceted aspects of how glucomannan exerts its anti-tumor function.